Meningkatkan Jiwa Kewirausahaan dan Kreativitas Masyarakat Melalui Sosialisasi dan Pelatihan Pembuatan Kokedama Berbahan Dasar Limbah Serabut Kelapa di Kelurahan Tiwugalih, Kabupaten Lombok Tengah.: Optimalisasi Sumber Daya Alam Menjadi Produk Unggulan di Kelurahan Tiwu Galih - Baiq Nindy Anidia Agustina; Baiq Rani Dewi Wulandani; Lalu Alfin Maulana Ramdani; Ismi Wardhani; Ahmad Beni Baharun; Aris Munandar; Muhammad Ulhusna; Baiq Silvia Wahyu Ning Tyas; Era Anggela; Annisa Rahmatia; Tamlihatul Khalisah (Universitas Mataram, 2022)
The Mataram University Thematic Real Work Lecture Group held outreach activities and training on making kokedama made from coconut fiber. This activity was carried for one day at 15 july 2022 . Located in Tiwugalih Village, Central Lombok Regency. With support and cooperation of the Tiwugalih sub-district government, this activity was carried out well and with great enthusiasm from the local community. This activity is carried out to improve the entrepreneurial spirit of the Tiwugalih Village community and educate the Tiwugalih Village community to manage coconut factory waste in the area.Keyword : Tiwugalih Village, Kokedama, Training.